Badania materiałów stosowanych do uzupełniania ubytków zapraw w malowidłach na płótnie - Łękawa-Wysłouch, Teresa (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2010)
The paper presents the description and results of the research on materials used or potentially suitable for reintegration of the injuries of priming in paintings on canvas. Five ready-made brand products have been tested and compared them with two products made by the recipes aiming for determination of their physical and chemical properties as well as suitability in conservation of easel paintings on canvas supports. The following research procedures were followed: the analysis of chemical composition – using Differential Thermal Analysis (DTA) as well as IR-spectroscopy; the evaluation of preparation, application and other of handling properties; suitability for imprinting the texture on the surface of fi lling using negative moulds of artifi cial resins; evaluation of shrinkage and cracking during drying of the material applied to canvas support; the adhesion to canvas sized with methyl cellulose and saturated with bees-wax-and resin mixture; determination of pH of fresh, cured and aged materials; elasticity of fi llings on canvas bent on cylinders of various diameter in different humidity and temperature conditions; hygroscopic properties in high humidity atmosphere; absorbability and wettability of the fi lling surface with aqueous binding media of paints; adhesion of layers of paints with water-based media resistance to biodegradation in high humidity atmosphere; ageing resistance in extreme air temperature and humidity; reversibility – the possibility to remove the fi llings after several months of aging in extreme air temperature and humidity – with mechanical and chemical methods.